Fluorogenic sydnonimine probes for orthogonal labeling. Issue 30 (21st March 2022) - Xu, Wenyuan; Shao, Zhuzhou; Tang, Cheng; Zhang, Chun; Chen, Yinghan; Liang, Yong
Abstract : Sydnonimine fluorogenic probes with a high turn-on ratio were designed and synthesized, releasing near-infrared fluorescence via a strain-promoted "click-and-release" reaction. Abstract : A FRET-based fluorescence turn-on probe is designed, which employs a sydnonimine as the linker to match specific fluorophore and quencher pairs and releases the fluorescence after the "click-and-release" reaction. Furthermore, we realized selective fluorescence labeling by exploiting the mutual orthogonality between sydnonimine–DIBAC and tetrazine–1, 3-Cp cycloaddition pairs.